Poplarism : the Truth about the Poplar Scale of Relief and the Action of the Ministry of Health - Lansbury, Edgar (London : Independent Labour Party)
1924 1924 1920s 8 pages "Poplarism" The Truth about the Poplar Scale of Relief and the Action of the Ministry of Health. By EDGAR LANSBURY Chairman of the Poplar Board of Guardians. ILP INDEPENDENT LABOUR PARTY PUBLICATION DEPARTMENT 308 GRAY'S INN ROAD, LONDON, W.C.1 15X/2/209/47